Методи та інструментарій діагностики та оцінки стратегій та стратегічних альтернатив аграрних підприємств - Михальчук, Олександр Вячеславович аспірант; Mykhalchuk, Oleksandr (Запоріжжя : Видавничий дім «Гельветика», 2024)
UA: У статті розглядається роль стратегічного управління в аграрних підприємствах України в умовах сучасних викликів, таких як війна, зміни клімату та економічна нестабільність. Пояснюється, що стратегічне управління є процесом розробки, реалізації та оцінки стратегій, спрямованих на досягнення довгострокових цілей організації, зокрема в аграрному секторі. Окрему увагу приділено етапам стратегічного управління, зокрема аналізу зовнішнього та внутрішнього середовища, розробці місії та цілей, а також вибору стратегій розвитку підприємства. Визначено два основних типи стратегій – активні та пасивні, а також наведено основні методи та інструменти стратегічного планування, зокрема SWOT-, PEST-, GAP- та BCG-аналіз. Окремо досліджено важливість формування портфеля стратегічних альтернатив і вибору оптимальної стратегії розвитку агропідприємства, що дозволяє адаптувати діяльність підприємств до змінюваного ринкового середовища. Стаття також підкреслює значення ефективної реалізації стратегій та контролю за їх виконанням для досягнення сталого розвитку та конкурентоспроможності агропідприємств в умовах глобальних змін. /// EN: The article explores the critical role of strategic management in agricultural enterprises in Ukraine, particularly in the face of contemporary challenges such as war, climate change, and economic instability. It highlights how strategic management serves as a fundamental process that involves developing, implementing, and evaluating strategies designed to achieve long-term organizational objectives, with a specific focus on the agricultural sector. The paper emphasizes the importance of strategic planning for agricultural enterprises, especially when dealing with a dynamic and unpredictable external environment. The article examines the key stages of strategic management, including the analysis of both the external and internal environments, the formulation of the enterprise’s mission and goals, and the selection of appropriate development strategies. It outlines the significance of comprehensive situational analysis tools such as SWOT-analysis (Strengths, Weaknesses, Opportunities, Threats), PEST-analysis (Political, Economic, Social, Technological factors), GAP-analysis (identifying discrepancies between actual and desired performance), and BCG-analysis (Boston Consulting Group matrix). These tools are critical in assessing market conditions, competition, and identifying potential opportunities or threats, all of which are essential for creating a viable strategy. The article emphasizes that the formation of a strategic alternatives portfolio is an essential aspect of strategic management. This portfolio allows enterprises to adapt their operations to changing market conditions and external shocks, ensuring that the agricultural sector can remain resilient and competitive. Additionally, the study stresses the importance of the effective implementation and monitoring of strategies. The continuous evaluation of the performance of implemented strategies is crucial to ensure that the organization remains on track to meet its objectives. The role of strategic management in fostering sustainable development is particularly important, as agricultural enterprises must balance economic performance with environmental stewardship and social responsibility. In conclusion, the article asserts that strategic management is a key driver for the competitiveness and long-term sustainability of agricultural enterprises in Ukraine, especially amidst global challenges and uncertainty. By adopting comprehensive strategic planning methodologies and maintaining flexibility, agricultural businesses can not only survive but thrive in an increasingly volatile world. This study contributes to understanding how strategic management can help agricultural enterprises navigate through crises and achieve sustainable growth in the long run.
Methods and tools for diagnostic and assessment of strategies and strategic alternatives of agricultural enterprises
Keywords: стратегічне управління; аграрні підприємства; стратегія розвитку; стратегічне планування; адаптація; конкуренція; сталий розвиток; агросектор; економічна стабільність; портфель стратегічних альтернатив; strategic management; agricultural enterprises; development strategy; strategic planning; adaptation; competition; sustainable development; agricultural sector; economic stability; portfolio of strategic alternatives